A review of the cytotaxonomy of Kalanchoe (Crassulaceae subfam. Kalanchooideae) with reference to evolutionary trends in the genus - Smith, Gideon F. (Phytotaxa, 2022)
Over a 60-year period in the mid-20th century (ca. mid-1930s to mid-1990s), chromosome numbers, reflected as either x, n, or 2n, or a combination of these, were published for just more than 80 species, infraspecific taxa, and nothospecies of Kalanchoe (Crassulaceae subfam. Kalanchooideae), so representing counts for about ⅓ of the taxa at present recognised in the genus. All published chromosome numbers that could be traced for Kalanchoe taxa are here catalogued and discussed in a classificatory framework, as well as from a horticultural breeding perspective, given the persisting—indeed expanding—global popularity of kalanchooid selections, cultivars, and hybrids, especially as indoor plants, as outdoor plants in mild climates, and even as cutflowers. With the exception of very few of the chromosome numbers previously reported for Kalanchoe, they are all divisible by 17, 18, or 20; of these basic numbers (x), 17 is often presented as primary. In this survey, haploid numbers (n) were most often recorded as 17, 18, 20, and 51; and 2n as 34, 36, and 40 (all diploid); or as 68 or 72 (both tetraploid), but with 51 (triploid), 102 (hexaploid), 140 (octoploid), and 176 (decaploid) also documented. The analysis of available cytogenetic information presented here for Kalanchoe provides support for the recognition of K. subg. Alatae and, in the autonymic K. subg. Kalanchoe, for a ‘woody clade’, and in the woody clade, for K. sect. Stellatopilosae.